2017
DOI: 10.3727/096368916x694364
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β Inhibition Induced Neuroprotection, Regeneration, and Functional Recovery after Intracerebral Hemorrhagic Stroke

Abstract: Hemorrhagic stroke is a devastating disease that lacks effective therapies. In the present investigation, we tested 6-bromoindirubin-3'-oxime (BIO) as a selective glycogen synthase kinase-3β (GSK-3β) inhibitor in a mouse model of intracerebral hemorrhage (ICH). ICH was induced by injection of collagenase IV into the striatum of 8- to 10-week-old C57BL/6 mice. BIO (8 μg/kg, IP) was administered following either an acute delivery (0-2 h delay) or a prolonged regimen (every 48 h starting at 3 days post-ICH). At 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Immunohistochemistry was performed as described before (Zhao et al, ). Mice were sacrificed by CO 2 overdose 35 days after AAV injection.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as described before (Zhao et al, ). Mice were sacrificed by CO 2 overdose 35 days after AAV injection.…”
Section: Methodsmentioning
confidence: 99%
“…Convincingly establishing a role for GSK3␤ in stroke pathology, Kelly et al (2004) showed that inhibition of GSK3␤ with CXhir025 in both OGD in vitro and in vivo rat middle cerebral artery occlusion (MCAO) models increased neuronal cell survival. In the intracerebral hemorrhage mouse model, 6-bromoindirubin-3Ј-oxime, a selective GSK-3␤ inhibitor, acutely administered, reduced hematoma volume by attenuating the expression of GSK-3␤ phosphorylation/activation, which increased the viability of neurons and other cell types (Zhao et al, 2017). These findings suggest that the wnt/GSK-3␤/ ␤-catenin pathway may be further explored for treatment in the pathology of stroke.…”
Section: Introductionmentioning
confidence: 90%
“…In this regard, the intraperitoneal delivery of 6-BIO, a GSK3β inhibitor, improved neurological functions, reduced brain hematoma volume, and stimulated regeneration after ICH (Zhao et al, 2017). This was attributed to an upregulation of BDNF, which stimulates the proliferation and migration of neuronal progenitors from the SVZ toward the injured zone, thus increasing the number of newborn neurons within in the peri-hematomal brain region (Zhao et al, 2017). 6-BIO also improved angiogenesis by an increase number of BrdU + /GLUT1 + cells in the peri-hematomal zone during the second phase of hemorrhagic stroke (Zhao et al, 2017).…”
Section: Implication In Hemorrhagic Stroke Therapymentioning
confidence: 99%
“…In both studies, SAH was associated to a deactivation of the canonical Wnt pathway translated by reduced levels of Wnt1, Wnt3a and Fzd1. In this regard, the intraperitoneal delivery of 6-BIO, a GSK3β inhibitor, improved neurological functions, reduced brain hematoma volume, and stimulated regeneration after ICH (Zhao et al, 2017). This was attributed to an upregulation of BDNF, which stimulates the proliferation and migration of neuronal progenitors from the SVZ toward the injured zone, thus increasing the number of newborn neurons within in the peri-hematomal brain region (Zhao et al, 2017).…”
Section: Implication In Hemorrhagic Stroke Therapymentioning
confidence: 99%
See 1 more Smart Citation